Sustaining a New Model of Acute Stroke Care: A Mixed-Method Process Evaluation of the Melbourne Mobile Stroke Unit - Kathleen L. Bagot; Tara Purvis; Shaun Hancock; Henry Zhao; Skye Coote; Damien Easton; Bruce CV Campbell; Stephen M. Davis; Geoff A. Donnan; Shane Foster; Francesca Langenberg; Karen Smith; et al. (Kerman University of Medical Sciences, 2023)
Background  Internationally, Mobile Stroke Unit (MSU) ambulances have changed pre-hospital acute stroke care delivery. MSU clinical and cost-effectiveness studies are emerging, but little is known about important factors for achieving sustainability of this innovative model of care.Methods  Mixed-methods study from the Melbourne MSU (operational since November 2017) process evaluation. Participant purposive sampling included clinical, operational and executive/management representatives from Ambulance Victoria (AV) (emergency medical service provider), the MSU clinical team, and receiving hospitals. Sustainability was defined as ongoing MSU operations, including MSU workforce and future model considerations. Theoretically-based on-line survey with Unified Theory of Acceptance and Use of Technology (UTAUT), Self Determination Theory (SDT, Intrinsic Motivation), and open-text questions targeting barriers and benefits was administered (June-September 2019). Individual/group interviews were conducted, eliciting improvement suggestions and requirements for ongoing use. Descriptive and regression analyses (quantitative data) and directed content and thematic analysis (open text and interview data) were conducted.Results  There were 135 surveys completed. Identifying that the MSU was beneficial to daily work (β = 0.61), not experiencing pressure/tension about working on the MSU (β = 0.17) and thinking they did well working within the team model (β = 0.17) were significantly associated with wanting to continue working within the MSU model [R2 = 0.76; F(15, 60) = 12.76, P < .001]. Experiences varied between those on the MSU team and those working with the MSU. Advantages were identified for patients (better, faster care) and clinicians (interdisciplinary learning). Disadvantages included challenges integrating into established systems, and establishing working relationships. Themes identified from 35 interviews were MSU team composition, MSU vehicle design and layout, personnel recruitment and rostering, communication improvements between organisations, telemedicine options, MSU operations and dispatch specificity.Conclusion  Important factors affecting the sustainability of the MSU model of stroke care emerged. A cohesive team approach, with identifiable benefits and good communication between participating organisations is important for clinical and operational sustainability.